Absenteeism in apprenticeships : What role do works councils play? - Pfeifer, Harald [Verfasser] (My University, 2014)
"This paper examines the influence of works councils on apprentices' absence from the workplace in Germany. The analysis draws on merged administrative and survey data, including information on the cumulated days apprentices are absent from work due to sickness. On average, apprentices are absent 9 working days per year, whereas strong differences exist with respect to the training occupation and several firm characteristics. Regression results imply that the presence of a works council in a firm significantly reduces apprentices' absence. This result supports the hypothesis that works councils effectively exercise their legally anchored 'voice' function in the German apprenticeship system." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.5.4 Sozialpartner; Betriebliche Berufsausbildung; Fehlzeiten; Betriebsrat; Einflussfaktor; Regressionsanalyse